2020
DOI: 10.1128/mbio.02949-19
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Resistance Pathway for Calcineurin Inhibitors in the Human-Pathogenic Mucorales Mucor circinelloides

Abstract: Mucormycosis is an emerging lethal fungal infection in immunocompromised patients. Mucor circinelloides is a causal agent of mucormycosis and serves as a model system to understand genetics in Mucorales. Calcineurin is a conserved virulence factor in many pathogenic fungi, and calcineurin inhibition or deletion of the calcineurin regulatory subunit (CnbR) in Mucor results in a shift from hyphal to yeast growth. We analyzed 36 calcineurin inhibitor-resistant or bypass mutants that exhibited hyphal growth in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 85 publications
(113 reference statements)
0
32
0
1
Order By: Relevance
“…When M. circinelloides is grown in the presence of FK506 it exhibits yeast growth instead of hyphae which shows that calcineurin regulates dimorphism in this fungus (hyphal to yeast transition) (Lee et al, 2013). Mutants lacking functional calcineurin are less virulent than the wild type which suggests that calcineurin is a key target for the treatment of mucormycosis (Lee et al, 2013(Lee et al, , 2015Vellanki et al, 2020). M. circinelloides encodes three calcineurin catalytic subunits (CnaA, CnaB, and CnaC) and one regulatory subunit (CnbR) (Lee et al, 2013).…”
Section: Mucor Circinelloidesmentioning
confidence: 99%
See 1 more Smart Citation
“…When M. circinelloides is grown in the presence of FK506 it exhibits yeast growth instead of hyphae which shows that calcineurin regulates dimorphism in this fungus (hyphal to yeast transition) (Lee et al, 2013). Mutants lacking functional calcineurin are less virulent than the wild type which suggests that calcineurin is a key target for the treatment of mucormycosis (Lee et al, 2013(Lee et al, , 2015Vellanki et al, 2020). M. circinelloides encodes three calcineurin catalytic subunits (CnaA, CnaB, and CnaC) and one regulatory subunit (CnbR) (Lee et al, 2013).…”
Section: Mucor Circinelloidesmentioning
confidence: 99%
“…It was first reported in C. neoformans that the mutants lacking calcineurin do not survive in conditions that mimic the host environment (Steinbach et al, 2007). Further studies have shown that calcineurin is also required for virulence and pathogenicity in C. albicans (Blankenship et al, 2003;Blankenship and Heitman, 2005), A. fumigatus (Steinbach et al, 2006), and Mucor circinelloides (Lee et al, 2013;Lee et al, 2015;Vellanki et al, 2020). Although, calcineurin is an attractive target for antifungal drug development, there are two key problems.…”
Section: Introductionmentioning
confidence: 99%
“…Mucor stimulates yeast growth, even in aerobic conditions (Kubo & Mihara, 2007;Orlowski, 1991). Accordingly, it has been reported that in M. circinelloides, intracellular cAMP accumulation is higher in yeast compared to hyphal growth (Vellanki et al, 2020). In eukaryotes, it has been reported that cAMP activates the protein kinase A (PKA) pathway by binding to the regulatory subunit (PkaR) that leads to its dissociation from the catalytic subunit (PkaC), which activates several transcription factors that control the final morphological fate of the cell (Choi, Jung, & Kronstad, 2015).…”
Section: The Addition Of Camp To Cultures Of Diverse Dimorphic Speciementioning
confidence: 99%
“…In this context, most of the current research is based on searching for and characterizing new targets in the physiology of Mucorales that could serve for the development of new antifungal compounds. Different research lines study the role of virulence factors described in Mucorales pathogenesis, such as the CotH proteins, the three components of the high-affinity iron uptake system, and the regulatory proteins involved in dimorphism [ 6 , 7 , 8 , 9 , 10 ]. In addition, several genome-wide strategies have been designed to find new and specific targets in Mucorales, based on the RNAi mechanism of the fungus [ 11 ] and in the host–pathogen transcriptome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%